Deep Dark Futures: Foresighting Human Impacts on Mesopelagic Ecosystem Services - Ben Scoulding; Alistair J. Hobday; Rowan Trebilco; Heidi Pethybridge; Ingrid van Putten; Katherine Baker; Karen Evans; David Green; Eriko Hoshino; Haris Kunnath; Clothilde Langlais; Tim P. Lynch; et al. (Fish and Fisheries, 2026)
Most of the global mesopelagic zone lies beyond the jurisdiction of any single government or entity, making equitable access and sustainable management for ecosystem services (ES) difficult. Here, a foresighting approach was used to examine the plausible consequences of four speculative scenarios of human activity on the mesopelagic zone and its associated ES. Large‐scale Harvest represented the provisioning ES, with concerns over unsustainable removal of mesopelagic biota. Climate Mitigation, a regulating ES, involved harvesting and then dumping mesopelagic biota to maximise carbon drawdown. In Geopolitical Manoeuvring, the scenario focused on cultural ES; mesopelagic fisheries were used as a geopolitical instrument to assert claims over ocean spaces. Finally, Mineral Extraction, a supporting ES, considered the impact of deep‐sea mining on mesopelagic ecosystems. Drivers and indicators for each scenario were identified, and qualitative network models were created to assess impact on the different system components using press perturbations. Model outputs highlighted the central role that mesopelagic biota play in supporting and regulating other ecosystem components and the likely negative impacts of reduced biomass on higher order predators and ocean carbon storage. Interestingly, biological indicators performed poorly as early warning signals of change across all scenarios; instead, the most effective indicators were related to science and technology, economics and governance. International agreements for sustainable use of the mesopelagic zone are needed to avoid loss of ES underpinning all scenarios. While this foresighting focused on the mesopelagic zone, the approach of developing scenarios, models and indicators has broader applicability to studies of other systems.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Engineering Performance and Spatial Models Highlight Key Considerations for Supporting Broadscale Replacement of Environmentally Sensitive (ES) Vessel Moorings - Lincoln S. Wong; Andrew Martini; Tim P. Lynch; Carlie Devine; Lauren Hardiman; Felicity R. McEnnulty; Rick D. Stuart-Smith; D. Jeff Ross (Coastal Management, 2025)

Population parameters and conservation implications for one of the world's rarest marine fishes, the red handfish ( Thymichthys politus ) - Tyson J. Bessell; Rick D. Stuart‐Smith; Olivia J. Johnson; Neville S. Barrett; Tim P. Lynch; Andrew J. Trotter; Jemina Stuart‐Smith (Journal of Fish Biology, 2024)
Population estimates are required for effective conservation of many rare marine species, but can be difficult to obtain. The critically endangered red handfish ( Thymichthys politus ) is a coastal anglerfish known only from two fragmented populations in southeast Tasmania, Australia. It is at a high risk of extinction due to low numbers, loss of habitat, and the impacts of climate change. To aid conservation efforts, we provide the first empirical population size estimates of red handfish and investigate other important aspects of the species' life history, such as growth, habitat association, and movement. We surveyed both red handfish local populations via underwater visual census on scuba over 3 years and used photographic mark‐recapture techniques to estimate biological parameters. In 2020, the local adult population size was estimated to be 94 (95% confidence interval [CI] 40–231) adults at one site, and 7 (95% CI 5–10) at the other site, suggesting an estimated global population of 101 adults. Movement of individuals was extremely limited at 48.5 m (± 77.7 S.D. ) per year. We also found evidence of declining fish density, a declining proportion of juveniles, and increasing average fish size during the study. These results provide a serious warning that red handfish are likely sliding toward extinction, and highlight the urgent need to expand efforts for ex situ captive breeding to bolster numbers in the wild and maintain captive insurance populations, and to protect vital habitat to safeguard the species' ongoing survival in the wild.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Sex-based divergence in tidal, lunar and seasonal cycles of activity in the olive sea snake, Aipysurus laevis (Elapidae, Hydrophiinae) - Tim P. Lynch; Ross A. Alford; Richard Shine (Coral Reefs, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Conservation of the Critically Endangered Eastern Australian Population of the Grey Nurse Shark (Carcharias taurus) Through Cross-Jurisdictional Management of a Network of Marine-Protected Areas - Tim P. Lynch; Robert Harcourt; Graham Edgar; Neville Barrett (Environmental Management, 2013)

The Difference between Spatial and Temporal Variation in Recreational Fisheries for Planning of Marine Protected Areas: Response to Steffe - TIM P. LYNCH (Conservation Biology, 2008)

Incorporation of Recreational Fishing Effort into Design of Marine Protected Areas - TIM P. LYNCH (Conservation Biology, 2006)
Theoretical models of marine protected areas (MPAs) that explore benefits to fisheries or biodiversity conservation often assume a dynamic pool of fishing effort. For instance, effort is homogenously distributed over areas from which subsets of reserves are chosen. I tested this and other model assumptions with a case study of the multiple‐use Jervis Bay Marine Park. Prior to zoning of the park I conducted 166 surveys of the park's recreational fisheries, plotting the location of 16,009 anglers. I converted these plots into diagrams of fishing effort and analyzed correlates between fishing and habitat and the effect of two reserve designs—the draft and final zoning plans of the park—on the 15 fisheries observed. Fisheries were strongly correlated with particular habitats and had negatively skewed and often bimodal spatial distribution. The second mode of intensely fished habitat could be 6 SD greater than the fishery's mean allocation of effort by area. In the draft‐zoning plan, sanctuary zone (no‐take) area and potential subduction of fishing effort were similar. In the final plan, which was altered in response to public comment, the area of sanctuary zone increased, and the impact on fishing effort decreased. In only one case was a fishery's most intensely targeted location closed to fishing. Because of the discriminating manner with which fishers target habitats, if simple percentage targets are used for planning, sanctuary location can be adjusted to avoid existing fishing effort. According to modeled outcomes, the implication of this may be diminished reserve effectiveness. To address this, reserve area should be implicitly linked to subducted fishing effort when promoting or modeling MPAs.

Conflict and Impacts of Divers and Anglers in a Marine Park - Tim P. Lynch; Elizabeth Wilkinson; Louise Melling; Rebecca Hamilton; Anne Macready; Sue Feary (Environmental Management, 2004)